NUAK family kinase 2 is a novel therapeutic target for prostate cancer. Issue 3 (24th November 2021) - Fu, Weiwei; Zhao, Megan T.; Driver, Lucy M.; Schirmer, Amelia U.; Yin, Qi; You, Sungyong; Freedland, Stephen J.; DiGiovanni, John; Drewry, David H.; Macias, Everardo
Abstract: Current advancements in prostate cancer (PC) therapies have been successful in slowing PC progression and increasing life expectancy; however, there is still no curative treatment for advanced metastatic castration resistant PC (mCRPC). Most treatment options target the androgen receptor, to which many PCs eventually develop resistance. Thus, there is a dire need to identify and validate new molecular targets for treating PC. We found NUAK family kinase 2 (NUAK2) expression is elevated in PC and mCRPC versus normal tissue, and expression correlates with an increased risk of metastasis. Given this observation and because NUAK2, as a kinase, is actionable, we evaluated the potential of NUAK2 as a molecular target for PC. NUAK2 is a stress response kinase that also plays a role in activation of the YAP cotranscriptional oncogene. Combining pharmacological and genetic methods for modulating NUAK2, we found that targeting NUAK2 in vitro leads to reduction in proliferation, three‐dimensional tumor spheroid growth, and matrigel invasion of PC cells. Differential gene expression analysis of PC cells treated NUAK2 small molecule inhibitor HTH‐02‐006 demonstrated that NUAK2 inhibition results in downregulation of E2F, EMT, and MYC hallmark gene sets after NUAK2 inhibition. In a syngeneic allograft model and in radical prostatectomy patient derived explants, NUAK2 inhibition slowed tumor growth and proliferation rates. Mechanistically, HTH‐02‐006 treatment led to inactivation of YAP and the downregulation of NUAK2 and MYC protein levels. Our results suggest that NUAK2 represents a novel actionable molecular target for PC that warrants further exploration.